La fabrique des mères imaginaires dans les séries télévisées françaises (1992-2012) - Sarah Lécossais (Genre, Sexualité et Société)
This paper shows that French TV shows construct a hegemonic mother figure (a caring, loving, listening one…) which has to be analysed in terms of gender, race, sexuality or profession. Indeed heroines are rarely non-white, lesbians or happily unemployed. An intersectional analysis shows that this hegemonic figure of motherhood is also a normalized figure of what a “good” mother is expected to be: white, heterosexual and engaged in some professional activity. These shows feed a normative imaginary of motherhood and an imagined identity through exoticization’s processes of non-white characters.